The necessity of diversion of juvenile offenders from the criminal justice system in Malaysia / Ahmad Waseem Dhihny Yunus and Adi Aizat Yajid - Yunus, Ahmad Waseem Dhihny; Yajid, Adi Aizat (2014)
The dealing of juvenile offenders through formal court process has caused problems of stigmatization and further development of deviant behavior due to the absorption into the criminal justice system. The absence of legislation providing for diversionary measures is a challenge faced by our country. This article aims to discuss and analyze the necessity of diverting juvenile offenders from the criminal justice system in Malaysia. This article also discuss the strengths and weaknesses of the current legislation which is the Criminal Procedure Code and consequently aims to seek reform to the current law in reference to the diversionary measures embedded in the law of New South Wales, specifically the Young Offenders Act 1997 (New South Wales).